(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
Entrepreneurship is recognized as a crucial factor in the transformation of nations politically and socio-economically. Despite growth in MSME contribution to Malaysia's GDP, the pandemic has reversed the trend, and various government agencies are working to revitalize the MSME ecosystem. This study aimed to investigate the relationship between market network, family support, government policy, and entrepreneurs’ performance among MADA entrepreneurs. Data were collected through a survey questionnaire from 145 entrepreneurs operating in MADA region. Correlation and multiple regression analyses were conducted to analyze the data. The results showed that market network, family support, and government policy had a significant positive relationship with entrepreneurs’ performance. Among these factors, government policy had the highest impact on entrepreneurs’ performance. These findings suggest that policymakers and entrepreneurs should pay attention to the role of government policy in supporting and promoting entrepreneurship. Furthermore, this study provides a basis for future research to investigate other variables that may influence entrepreneurs’ performance, such as education, experience, and financial factors.